International organizations : principles and issues - Bennett, A. LeRoy, 1914- (Alvin LeRoy) (Upper Saddle River, NJ : Prentice Hall, 2002)
For upper-level undergraduate and graduate-level courses dealing with International Organizations, the United Nations, and the UN System. This comprehensive, historical, institutional, and functional/programmatic analysis of the development of contemporar
Preface. 1. Introduction. 2. A Great Experiment: The League of Nations. 3. The Genesis of the United Nations. 4. Basic Principles and Organization of the United Nations. 5. Basic Structure and Operations of t.
Includes bibliographical references and index.
Keywords: International agencies; International organization; Regionalism (International organization).; Uluslararası kurumlar; Uluslararası örgüt; Bölgecilik (Uluslararası örgüt).